![\text{ 36 }km^2](https://img.qammunity.org/2023/formulas/mathematics/college/ihpwxo35vshcplh1w0ilmvwp4svxrwjf90.png)
Step-by-step explanation
the surface area of a square pyramid is given by:
![\begin{gathered} sa=A+(1)/(2)ps \\ \text{where A is the area of the base} \\ p\text{ is the perimeter of the base} \\ s\text{ is the }slant\text{ heigth} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xp87yhifj4ad0bgzowtzrb62ywm6fc9z68.png)
so
Step 1
area of the base
the baseis a square, so the area is
![\begin{gathered} Area=side^(^2) \\ Area_(base)=3km\cdot\text{ 3}km \\ Area_(base)=\text{ 9(}km^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tuof8fzaedvpqoszr7epvha6bw39mzk09w.png)
Step 2
perimeter of the base
the perimeter of a square is given by:
![\begin{gathered} \text{Perimeter}=\text{ 4}\cdot side \\ sp \\ \text{Perimeter}=\text{ 4}\cdot3km\text{ =12 }km \\ \text{Perimeter}=12km \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/evb3sn6xcp31fuy8dikh3dqthzjqqmm0ji.png)
Step 3
finally, let
![\text{slant heigth=5}km](https://img.qammunity.org/2023/formulas/mathematics/college/k0ufvn76upnjusb11xcq7zcs3qmz2tlrbi.png)
now, replace in the formula
![\begin{gathered} sa=A+(1)/(2)ps \\ sa=9(km^2)+(1)/(2)(12km)(5km) \\ sa=9(km^2)+30(km^2) \\ sa=39(km^2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u87in2gjuyhe58kd4w5sxzdkm4786peuj6.png)
therefore, the answer is
![\text{ 36 }km^2](https://img.qammunity.org/2023/formulas/mathematics/college/ihpwxo35vshcplh1w0ilmvwp4svxrwjf90.png)
I hope this helps you